PERANAN KOMUNIKASI PADA PROSES SUKSESI DI PERUSAHAAN KELUARGA STUDI PADA PT. CATUR PUTRA HARMONIS - Monika Teguh; Andrew Wijaya (LPPM Abdurrab Pekanbaru, 2020)
Indonesia is one of the countries whose economies are influenced by family businesses. A study states that 25% of Indonesia's Gross Domestic Product (GDP) is affected by family businesses. The high influence and role of family business in Indonesia makes the sustainability and growth of family business very important to be considered carefully. But the family company has a unique problem, that is company succession. Often the family business can only survive until the second or third generation, then can not develop further or even closed. Therefore a succession process is needed so that the family company does not have a bad ending. In this succession process, communication has a crucial role. One of the family companies that has managed in making succession by maximizing communication is PT Catur Putra Harmonis. The Makassar-based family company has not only succeeded in maintaining its business across generations, but has also been able to expand the business more broadly. Communication has a role in various stages of succession including the provision of knowledge about the company, training, work trials, meetings with stakeholders, and performance accountability. Cross-generation communication becomes the main key so that the succession process can run well and smoothly.